Іmpact of Ukraine-Russia war on global trade and development: an empirical study - Mahesh Kumar Singh; Sárközy Helga; Suraj Kumar Singh; Zéman Zoltán (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. The crisis in Ukraine has created a humanitarian crisis of immense proportions and has also dealt a severe blow to the globe economy. The brunt of the suffering and destruction are being felt by the people of Ukraine themselves but the prices in terms of reduced trade and output are likely to be felt by people round the world through higher food and energy prices and reduced availability of products exported by Russia and Ukraine. Poorer countries are at high risk from the war, since they have a tendency to spend a bigger fraction of their incomes on food compared to wealthier countries, this might impact huge political stability globally. From a macroeconomic perspective, higher prices for food and energy will reduce real incomes and depress global import demand. Sanctions will impose economic costs on not only Russia directly but also on its trading partners. Besides Russia and Ukraine, depressed gross domestic product (GDP) will probably be seen mostly in Europe given the region’s geographic proximity and its dependence on Russian energy. Trade costs will rise within the near term because of extraordinary sanctions, export restrictions, higher energy costs and transport disruptions furthermore. As a result, the impact of the war will wear world interchange 2022 might be greater than the impact on global GDP. While shares of Russia and Ukraine in world trade and output are relatively small, they're important suppliers of essential products, notably food and energy. Both countries accounted for 2.5 percent in world merchandise trade and 1.9 per cent in world GDP in 2021. Yet they supplied around 25 per cent of wheat, 15 per cent of barley and 45 per cent of sunflower products exports in 2019. Russia alone accounted for 9.4 percent of world trade fuels, including a 20 per cent share in fossil fuel exports. Many countries are highly obsessed on food imports from Russia and Ukraine. for instance, over 1/2 wheat imports in Egypt, the Lebanon and Tunisia come from Russia and Ukraine. Other countries are more addicted to imports of fuels from Russia, like Finland (63 percent) and Turkey (35 percent). Russia and Ukraine also are key providers of inputs into industrial value chains. Russia is one in all the most suppliers globally of palladium and rhodium, key inputs within the production of catalytic converters within the automotive sector and therefore the manufacture of semiconductors. Semiconductor production also depends to a considerable extent on neon supplied by Ukraine, which further provides variety of low-tech products to the ecu automobile value chain, like wire harnesses. Prolonged disruptions within the supply of those goods could harm the recovery of automobile manufacturing. Sanctions are already having a robust impact on Russia’s economy, with possible medium to long-term consequences. Disconnecting Russian banks from the SWIFT settlement system and blocking Russia’s use of interchange reserves have triggered a pointy depreciation of the ruble, reducing real incomes within the country. Most of the massive international firms also are abandoning the Russian market. Oil and gas exports have yet to be strongly full of the sanctions, but the crisis could accelerate the worldwide transition towards greener energy sources. Longstanding economic relationships are disrupted by the war and by the sanctions imposed in its wake. Eminent economists have simulated various scenarios parenthetically the channels through which trade may well be affected and to explore possible short-run and long-run effects. Global trade growth is projected to slow by up to 2.2 percentage points in 2022. long term impacts could even be large and consequential. there's a risk that trade could become more fragmented in terms of blocs supported geopolitics. whether or not no formal blocs emerge, private actors might prefer to minimize risk by reorienting supply chains. this might reduce global GDP within the long term by about 5 percent, notably by restricting competition and stifling innovation (WTO, 2022). The Global Economy has a crucial role to play in mitigating the negative effects of the crisis and in rebuilding a post-war global economy. Keeping markets open are critical to confirm that economic opportunities remain receptive all countries. this can be very true within the post-war period, when businesses and families will have to repair their balance sheets and rebuild their lives. Through its importance for international trade and its monitoring, convening and other functions, the WTO is central to making sure that international trade continues to serve billions of individuals across the globe. during this paper we are giving an empirical analysis of world trade and development impacted by the present Russian-Ukraine war.

Резюме. Криза в Україні породила гуманітарну кризу величезних масштабів, а також завдала серйозного удару світовій економіці. Основний тягар страждань і руйнувань відчуває на собі сам народ України, але ціни в умовах скорочення торгівлі та виробництва, ймовірно, відчують на собі люди в усьому світі через підвищення цін на продукти харчування та енергоносії, а також зменшення доступності товарів, які експортує Росія і Україна. Бідніші країни піддаються високому ризику війни, оскільки вони, як правило, витрачають більшу частину своїх доходів на їжу порівняно з багатшими країнами, що може вплинути на величезну політичну стабільність у всьому світі. З макроекономічної точки зору, вищі ціни на продовольство та енергоносії призведуть до зменшення реальних доходів і глобального попиту на імпорт. Санкції завдадуть економічних збитків не лише безпосередньо Росії, а й її торговим партнерам. Окрім Росії та України, падіння ВВП, ймовірно, спостерігатиметься переважно в Європі, враховуючи географічну близькість регіону та його залежність від російських енергоносіїв. Торговельні витрати зростуть найближчим часом через надзвичайні санкції, експортні обмеження, високі витрати на енергоносії та перебої в транспорті. Як наслідок, вплив війни на світовий обмін у 2022 році може бути більшим, ніж вплив на світовий ВВП. Хоча частки Росії та України у світовій торгівлі та виробництві є відносно невеликими, вони є важливими постачальниками основних продуктів, зокрема продуктів харчування та енергії. У 2021 році на обидві країни припадало 2,5 відсотка світової торгівлі товарами та 1,9 відсотка світового ВВП. Проте у 2019 році вони постачали близько 25 відсотків пшениці, 15 відсотків ячменю та 45 відсотків експорту продуктів із соняшнику, 9,4 відсотка світової торгівлі паливом, у тому числі 20 відсотків експорту викопного палива. Багато країн дуже захоплені імпортом продуктів харчування з Росії та України, наприклад, понад 1/2 імпорту пшениці в Єгипет, Ліван і Туніс надходить з Росії та України. Інші країни більше залежні від імпорту палива з Росії, наприклад Фінляндія (63 відсотки) і Туреччина (35 відсотків). Росія та Україна також є ключовими постачальниками ресурсів для промислових ланцюжків створення вартості. Росія є одним із найбільших у світі постачальників паладію та родію, ключових сировинних ресурсів для виробництва каталітичних нейтралізаторів в автомобільному секторі, а отже, і для виробництва напівпровідників. Виробництво напівпровідників також значною мірою залежить від неону, що постачається Україною, який також забезпечує низку низько технологічних продуктів для автомобільного ланцюга створення вартості, наприклад джгути проводів. Тривалі перебої в постачанні цих товарів можуть зашкодити відновленню автомобілебудування. Санкції вже справляють сильний вплив на економіку Росії з можливими середньо- та довгостроковими наслідками. Відключення російських банків від розрахункової системи SWIFT і блокування використання Росією обмінних резервів спровокували різке знецінення рубля, скоротивши реальні доходи в країні. Більшість великих міжнародних фірм також покидають російський ринок. Експорт нафти та газу ще не сильно підпав під санкції, але криза може прискорити світовий перехід до більш екологічних джерел енергії. Тривалі економічні відносини порушуються війною та санкціями, запровадженими після неї. Видатні економісти змоделювали різні сценарії, вказавши в дужках канали, через які торгівля цілком може постраждати, і дослідити можливі короткострокові та довгострокові наслідки. Прогнозується, що зростання світової торгівлі сповільниться до 2,2 відсоткових пунктів у 2022 році. Довгостроковий вплив може бути навіть значним і непрямим, існує ризик того, що торгівля може стати більш фрагментованою з точки зору геополітики, що підтримується блоками. Незалежно від того, чи з’являться офіційні блоки, приватні суб’єкти можуть віддати перевагу мінімізації ризику шляхом переорієнтації ланцюгів постачання. Це може скоротити світовий ВВП у довгостроковій перспективі приблизно на 5 відсотків, зокрема через обмеження конкуренції та придушення інновацій (СОТ, 2022). Глобальна економіка відіграє вирішальну роль у пом’якшенні негативних наслідків кризи та у відбудові післявоєнної глобальної економіки. Збереження відкритих ринків має вирішальне значення для підтвердження того, що економічні можливості залишаються сприйнятливими для всіх країн. це може бути дуже вірним у післявоєнний період, коли підприємствам і родинам доведеться відновлювати свої баланси та будувати життя заново. Завдяки своїй важливості для міжнародної торгівлі та своїм функціям моніторингу, скликання та інших функцій СОТ відіграє центральну роль у забезпеченні того, щоб міжнародна торгівля продовжувала обслуговувати мільярди людей по всьому світу. У цій статті ми даємо емпіричний аналіз світової торгівлі та розвитку, на які вплинула нинішня російсько-українська війна.

Az ukrajnai válság óriási méretű humanitárius válságot idézett elő és súlyos csapást mért a világgazdaságra is. A szenvedés és pusztítás súlyát Ukrajna lakossága érzi, de a kereskedelem és a kibocsátás csökkenése miatti árváltozásokat valószínűleg az emberek világszerte érezni fogják a magasabb élelmiszer- és energiaárakban, valamint az Oroszország által exportált termékek szűkült elérhetősége miatt. A szegényebb országokat nagyobb veszély fenyegeti a háború miatt, mivel jövedelmük nagyobb hányadát költik élelmiszerre, mint a gazdagabb országok, ami óriási politikai változást hozhat világszerte. Makrogazdasági szempontból a magasabb élelmiszer- és energiaárak csökkentik a reáljövedelmeket és visszafogják a globális importkeresletet. A szankciók nemcsak közvetlenül Oroszországot, hanem kereskedelmi partnereit is gazdasági költségekkel sújtják. Oroszország és Ukrajna mellett a bruttó hazai termék (GDP) visszaesése valószínűleg leginkább Európában lesz tapasztalható, tekintettel a régió földrajzi közelségére és az orosz energiától való függésére. A kereskedelmi költségek rövid távon emelkedni fognak a rendkívüli szankciók, az exportkorlátozások, a magasabb energiaköltségek és a szállítási zavarok miatt. Ennek eredményeként a háború hatása a kereskedelemre 2022-ben nagyobb lesz, mint a globális GDP-re gyakorolt hatása. Míg Oroszország és Ukrajna részesedése a világkereskedelemben és a kibocsátásban viszonylag kicsi, attól még fontos beszállítói az alapvető termékeknek, különösen az élelmiszereknek és az energiának. Mindkét ország 2021-ben a világ árukereskedelmének 2,5 százalékát, a világ GDP-jének 1,9 százalékát adta. Ennek ellenére 2019-ben a búza, az árpa 15 százalékát és a napraforgótermékek 45 százalékát adták, a világkereskedelmi üzemanyagok 9,4 százalékát, ezen belül a fosszilis tüzelőanyagok exportjának 20 százalékát. Sok ország nagy mértékben függ az Oroszországból és Ukrajnából származó élelmiszerimporttól. Például Egyiptomba, Libanonba és Tunéziába a búzaimport több mint fele Oroszországból és Ukrajnából származik. Más országok jobban függenek az oroszországi üzemanyagimporttól, például Finnország (63 százalék) és Törökország (35 százalék). Oroszország és Ukrajna az ipari értékláncok kulcsfontosságú résztvevői. Oroszország világszerte az egyik legnagyobb palládium és ródium beszállítója, amelyek kulcsfontosságú szerepet töltenek be az autóipari katalizátorok gyártásában, és így a félvezetők gyártásában is. A félvezető gyártás jelentős mértékben függ az Ukrajna által szállított neontól is, amely további alacsony technológiájú termékek széles skáláját kínálja az autók gyártási láncának, mint például a kábelköteg. Az ilyen áruk ellátásának hosszan tartó fennakadása ronthatja az autógyártás fellendülését. A szankciók már most is erőteljes hatást gyakorolnak Oroszország gazdaságára, aminek közép- és hosszú távú következményei is lehetnek. Az orosz bankok leválasztása a SWIFT elszámolási rendszerről és a devizatartalékok orosz felhasználásának blokkolása a rubel erőteljes leértékelődését idézte elő, csökkentve az országon belüli reáljövedelmeket. A hatalmas nemzetközi cégek többsége is elhagyja az orosz piacot. Az olaj- és gázexport még nem telített meg a szankciókkal, de a válság felgyorsíthatja a zöldebb energiaforrásokra való világméretű átállást. A régóta fennálló gazdasági kapcsolatokat megzavarta a háború és az azt követő szankciók kivetése. Nívós közgazdászok különböző forgatókönyveket szimuláltak, hogy mely csatornákon keresztül a kereskedelem befolyásolható és hogy feltárják a lehetséges rövid és hosszú távú hatásokat. A globális kereskedelem növekedése az előrejelzések szerint akár 2,2 százalékponttal is lassulhat 2022-ben. A hosszú távú hatások akár jelentősek és következményesek is lehetnek - fennáll annak a veszélye, hogy a kereskedelem széttagoltabbá válhat a blokkok által támogatott geopolitika szempontjából. Ha kialakulnak formális blokkok, ha nem, a magánszereplők inkább az ellátási láncok átirányításával minimalizálják a kockázatot. Ez hosszú távon mintegy 5 százalékkal csökkentheti a globális GDP-t, nevezetesen a verseny korlátozásával és az innováció elfojtásával együtt (WTO, 2022). A globális gazdaságnak döntő szerepe van a válság negatív hatásainak enyhítésében és a háború utáni világgazdaság újjáépítésében. A piacok nyitva tartása kritikus fontosságú annak megerősítéséhez, hogy a gazdasági lehetőségek továbbra is fogékonyak maradnak minden országban. Ez nagyon igaz lehet a háború utáni időszakban, amikor a vállalkozásoknak és a családoknak meg kell javítaniuk helyzetüket és újjá kell építeniük életüket. A WTO a nemzetközi kereskedelemben betöltött fontossága, valamint nyomon követése, összehívása és egyéb funkciói révén központi szerepet játszik annak biztosításában, hogy a nemzetközi kereskedelem továbbra is emberek milliárdjait szolgálja szerte a világon. Ebben a cikkben empirikus elemzést adunk a világkereskedelemről és a jelenlegi orosz-ukrán háború által érintett fejlődésről.
Вплив українсько-російської війни на світову торгівлю та економічний розвиток: емпіричне дослідження
Az ukrán-orosz háború hatása a világkereskedelemre és a gazdasági fejlődésre: empirikus kutatás
https://aab-economics.kmf.uz.ua/aabe/issue/view/1
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010507
Keywords: international trade; global economy; GDP; crisis; sanctions